HUBUNGAN TINGKAT PENDIDIKAN DENGAN PENDAPATAN PETANI PADI DI KECAMATAN SAMPOINIET KABUPATEN ACEH JAYA - Zahara Wahyuni; Zulkifli Zulkifli (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to see how the education of rice farmers in Sampoiniet Subdistrict, Aceh Jaya Regency affects the income of farmers. The data used are primary data which are distributed questionnaires to 30 respondents with the technique of determining respondents random sampling. The model used by OLS. The results of this study indicate that farmer education has an effect on the income of rice farmers in Sampoiniet Subdistrict, Aceh Jaya Regency. Researchers suggest further research that examines supporting factors and inhibits the welfare of farmers in Aceh Jaya District, with more variables and samples.Keywords: Rice Famers, Famer Education, Income